2007
DOI: 10.1104/pp.107.110270
|View full text |Cite
|
Sign up to set email alerts
|

GeBP and GeBP-Like Proteins Are Noncanonical Leucine-Zipper Transcription Factors That Regulate Cytokinin Response in Arabidopsis  

Abstract: Understanding the role of transcription factors (TFs) is essential in reconstructing developmental regulatory networks. The plant-specific GeBP TF family of Arabidopsis thaliana (Arabidopsis) comprises 21 members, all of unknown function. A subset of four members, the founding member GeBP and GeBP-like proteins (GPL) 1, 2, and 3, shares a conserved C-terminal domain. Here we report that GeBP/GPL genes represent a newly defined class of leucine-zipper (Leu-zipper) TFs and that they play a redundant role in cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 60 publications
3
55
0
Order By: Relevance
“…2A). This indicates that the STKR1 N terminus is required for its interaction with the SnRK1 a-subunits.Previous studies have shown that STKR1/GeBP and its close homologs GPL1, GPL2, and GPL3 belong to a plant-specific family of transcription factors that form homodimers and heterodimers through their noncanonical Leu zipper motif located at the C terminus of the proteins (Chevalier et al, 2008). A direct interaction assay confirmed that STKR1 forms homodimers and heteromerizes with the GPL proteins via its C-terminal part (Fig.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…2A). This indicates that the STKR1 N terminus is required for its interaction with the SnRK1 a-subunits.Previous studies have shown that STKR1/GeBP and its close homologs GPL1, GPL2, and GPL3 belong to a plant-specific family of transcription factors that form homodimers and heterodimers through their noncanonical Leu zipper motif located at the C terminus of the proteins (Chevalier et al, 2008). A direct interaction assay confirmed that STKR1 forms homodimers and heteromerizes with the GPL proteins via its C-terminal part (Fig.…”
mentioning
confidence: 65%
“…2B), indicating that dimerization and SnRK1 interaction are mediated by different domains of the protein. Because STKR1/GeBP and GPL proteins have been proposed to act redundantly (Chevalier et al, 2008), we tested the ability of GPL1 and GPL3 to interact with SnRK1 in yeast. The data revealed that these proteins did not bind to the SnRK1 a-subunits, suggesting a specific functional relationship of STKR1 with SnRK1 (Fig.…”
Section: Stkr1 Binds Snrk1 Via Its N Terminusmentioning
confidence: 99%
“…Therefore, we deduced that a low threshold value existed for the transgenic gene product to realize the heterochronic and morphological responses observed in 35S::stk01-and 35S::stk03-transgenic tobacco. We and others [7] observed that STK-like proteins were able form homo-and heterodimers and therefore it appeared likely that also interactions occurred between transgenic Arabidopsis and resident tobacco STK-like proteins. To date, ten STK-like sequences have been identified in tobacco and deposited within the TOBFAC database.…”
Section: Plant Linementioning
confidence: 99%
“…More important with respect to the data presented, the overexpression of GEBP in Arabidopsis did not result in a phenotype deviating from the wild type [6]. Recently, GEBP and three STK-like proteins (At2g25650, At2g36340 and At5g14270, also termed GEBP-like proteins: GPL1, 2 and 3) were shown to form homoand heterodimers via unconventional leucine zipper motifs and to participate in the regulation of cytokinin response in Arabidopsis thaliana [7]. We have started characterizing stk-like genes after screening Arabidopsis expression libraries in the Yeast OneHybrid system using as a bait 700 bp of the 5´-silencer region within intron 2 of the Arabidopsis floral homeotic gene agamous (ag; [8] [GEBP]) when the plant-specific GAGA-factor BPC3 (At1g68120) was co-expressed in yeast (J.F.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation